Pengaruh Digital Leadership Terhadap Kreativitas Dan Dampaknya Pada Kinerja Karyawan Milenial: Peran Leader Member Exchange - Yolanda, Debora Icha Ester; Yulianti, Emma (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
This study aims to determine the effect of digital leadership on the level of creativity of millennial employees and its impact on employee performance. In addition, this study also considers the moderating role of Leader-Member Exchange (LMX) in managing the relationship between leaders and team members. Data was collected from 179 millennial employees, using a quantitative approach and Structural Equation Modeling (SEM) analysis technique using SmartPLS. This study uses the Structural Equation Modeling (SEM) analysis technique using SmartPLS which aims to test the relationship between variables, both among latent variables and with indicator variable. T-test results through the T-Statistics value of 1.421 with a P-Value of 0.155 prove that the LMX variable does not moderate the relationship between employee creativity and employee performance, so that suggestions for further research can change the LMX variable to a mediating variable for other variables.